Introducing Clyricidea Into Goat - Food Crops Mixed Farming in The Upland Areas - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1995)
ABSTRACT: Glyricidea, legume. trees (Giyricidca mactikaa), were introduced into food crop-goat nixed farming practiced by 20 farmers of Boyolali and Grobogan upland areas. In Trial I, farmers were planting a combination of corn and peanut fertilized by either 1) glyricidea. cut and carried from land terraces (Treatment I), 2) goat manure (Treatment II), and 3) urea and tri superphosphate (Treatment III) Partial budgeting showed that the use of glyrieidea as a fertilizer gave added values due to